Dabrafenib plus trametinib for compassionate use in metastatic melanoma: A STROBE-compliant retrospective observational postauthorization study. Issue 52 (December 2017) - Martín Algarra, Salvador; Soriano, Virtudes; Fernández-Morales, Luis; Berciano-Guerrero, Miguel-Ángel; Mujika, Karmele; Manzano, José Luis; Puértolas Hernández, Teresa; Soria, Ainara; Rodríguez-Abreu, Delvys; Espinosa Arranz, Enrique; Medina Martínez, Javier; Márquez-Rodas, Ivan; et al.
Abstract : Abstract: The main objective of the study was to evaluate the efficacy and safety of dabrafenib alone or combined with trametinib for compassionate use in patients with metastatic melanoma. This retrospective, observational study involved 135 patients with unresectable stage IIIC or stage IV melanoma from an expanded-access program at 30 Spanish centers. Forty-eight patients received dabrafenib monotherapy and 87 received combination dabrafenib and trametinib; 4.4% and 95.6% of the patients had stage IIIC and IV melanoma, respectively. All patients showed BRAF mutations in their primary or metastatic lesions; 3 were positive for V600K while the remainder had V600E or V600+. A positive response to treatment was reported in 89.3% of the patients. Overall survival rates at 12 and 24 months were 59.6% (95% confidence interval [CI], 52.5–68.9%) and 36.4% (95% CI, 27.8–45%), respectively. Progression-free survival rates at 12 and 24 months were 39.3% (95% CI, 31.1–47.5%) and 21.6% (95% CI, 14.5–28.7%), respectively. Fifty-seven patients (42.2%) reported cutaneous toxicity of any type, mainly hyperkeratosis (14.8%) and rash (11.9%). The most frequent adverse events were pyrexia (27.4%), asthenia (19.3%), arthralgia (16.9%), and diarrhoea (13.2%). Our results suggest that both dabrafenib alone or in combination with trametinib are effective for compassionate use in terms of response and/or survival rates. However, differences in patients' prognostic features ought to be considered. No new findings were revealed regarding the safety profiles of either regimen. This is the first study to evaluate the efficacy of these 2 selective BRAF and mitogen-activated extracellular signal-regulated kinase inhibitors in a real-world setting in Spain.